The EU self-surplus puzzle: an indication of VAT fraud? - Martin T. Braml; Gabriel J. Felbermayr (International Tax and Public Finance, 2021)
The world runs a trade surplus with itself: the reported values of exports exceed the reported values of imports. This is logically impossible but a well-known empirical fact. Less well-known is the fact that, in recent years, the EU has a trade surplus with itself that amounts to more than 80% of the global surplus. In this paper, we show that this EU self-surplus is worth a striking 307 billion Euro in 2018, equaling 1.9% of the Union's GDP, which persists both in goods and services trade accounts. We further examine discrepancies in goods and services trade accounts at the country and country pair level. These are strongest between neighboring countries and exist for members of the Euro Area as well as non-members. Around the 2004 Eastern Enlargement, the EU self-surplus quadrupled. Our estimations suggest that Cyprus, Ireland, Luxembourg, and Sweden are EU Members with the most inaccurate statistical regimes. We observe systematic biases which unlikely root in random measurement error. By contrast, we suspect that a large fraction of the EU's self-surplus puzzle seems related to fraud in value added tax (VAT). VAT exemptions for exporters provide strong incentives for the over-declaration of true export values. The resulting loss in tax income could amount to as much as 64 billion Euro per year.
Keywords: F36; F32; F24; H26; 340; Missing trade; VAT fraud; Statistical discrepancies; Current accounts